Koloniale Straßennamen Benennungspraktiken im Kontext kolonialer Raumaneignung in der deutschen Metropole von 1884 bis 1945 - Ebert, Verena (Koloniale und Postkoloniale Linguistik / Colonial and Postcolonial Linguistics (KPL/CPL), 2021)
This study examines colonially motivated street naming processes during the German Reich. It collects and analyses name structures and discursive functions in terms of the colonizing certainties that they verbalised. By combining innovative onomastics and discourse linguistics, this volume is the first to record and discuss global histories of entanglement using the example of the naming of public space in the German metropolis.